2019
DOI: 10.1155/2019/1242964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix Metalloproteinase 9 Serum Concentration as a Biomarker in Malignant Mesothelioma

Abstract: Background. Malignant mesothelioma (MM) is a rare, but fatal disease with few treatment options. The diagnosis and treatment response are challenging in MM. Therefore, the search for novel diagnostic and prognostic biomarkers is ongoing. The aim of our study was to investigate matrix metalloproteinase 9 (MMP9) as a potential serum biomarker of treatment response and survival in MM. We also investigated the influence of genetic polymorphisms on MMP9 serum levels. Methods. We included 110 patients with MM that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…These results suggest that Mo-TAMs modulate the remodeling of the extracellular matrix, creating a TME that is more permissive for tumor cell invasion. In support of this hypothesis, we observed that Mo-TAMs triggered a strong induction of MMP9 expression by MPM cells and clinical studies have reported that high expression of MMP9 correlates with a more aggressive MPM phenotype and decreased patients' survival [56,57].…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that Mo-TAMs modulate the remodeling of the extracellular matrix, creating a TME that is more permissive for tumor cell invasion. In support of this hypothesis, we observed that Mo-TAMs triggered a strong induction of MMP9 expression by MPM cells and clinical studies have reported that high expression of MMP9 correlates with a more aggressive MPM phenotype and decreased patients' survival [56,57].…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that there is evidence indicating that MMP-9 (rs17576) genotypes and haplotypes affect MMP-9 expression in obese children and in patients of African descent, suggesting that they may exert different effects, resulting in different and varied pathologies (7,22). Moreover, Štrbac et al suggest that serum MMP9 levels and polymorphisms should be studied as possible diagnostic and prognostic biomarkers for malignant mesothelioma (23). A significant difference was observed in the incidence of the rs17576 GG genotype between the case and control groups (po0.003).…”
Section: ' Discussionmentioning
confidence: 99%
“…In nowadays, several molecules, including estrogen receptors ( 5 ), matrix metalloproteinase 2 and 9 ( 6 , 7 ) have been reported as biomarkers for MPM. However, these factors were not available for early diagnosis due to lack of specificity.…”
Section: Introductionmentioning
confidence: 99%